Intelligent Ship Collision Avoidance Support System Based on the Algorithm of Anthropomorphic Physics - Feng, Guoxu; Gu, Songbo; Sun, Shihu (International journal of ambient computing and intelligence, 2024)
Most of the collision-related decisions of ships at sea depend on the working experience of drivers and determining a reasonable avoidance decision quickly when facing a multivessel encounter situation is difficult, so applying intelligent algorithms to assist these decisions is necessary. On the basis of this, the authors researched the construction of intelligent decision support systems for ship collision avoidance that relies on an anthropomorphic physics optimization algorithm. They used this algorithm to obtain the global range optimal solutions through iteration, which provides effective decisions for ship collision avoidance. The experiments were designed to simulate and analyze the ship collision avoidance decision model. The results showed that the decision-making system based on the anthropomorphic physics optimization algorithm can provide an effective collision avoidance decision scheme.